2003
DOI: 10.1002/humu.10254
|View full text |Cite
|
Sign up to set email alerts
|

Translocation and gross deletion breakpoints in human inherited disease and cancer I: Nucleotide composition and recombination-associated motifs

Abstract: Translocations and gross deletions are important causes of both cancer and inherited disease. Such gene rearrangements are nonrandomly distributed in the human genome as a consequence of selection for growth advantage and/or the inherent potential of some DNA sequences to be frequently involved in breakage and recombination. Using the Gross Rearrangement Breakpoint Database [GRaBD; www.uwcm.ac.uk/uwcm/mg/grabd/grabd.html] (containing 397 germ-line and somatic DNA breakpoint junction sequences derived from 219 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
244
2
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(260 citation statements)
references
References 188 publications
(214 reference statements)
13
244
2
1
Order By: Relevance
“…This confirms previous analysis of translocation breakpoints of which some have shown both GC-rich regions and polypyrimidine and polypurine tracts. 20,21 From our findings we suggest that the sequence similarities (80%) between the two chromosomes flanking the breakpoints as well as the surrounding polypurine and polypyrimidine tracts are predisposing factors for the reciprocal translocation. Recombination-associated sequence motifs have been shown to be over-represented at translocation breakpoints, including DNA polymerase core elements (frameshift hotspots) and heptamer recombination signals.…”
Section: Discussionmentioning
confidence: 60%
“…This confirms previous analysis of translocation breakpoints of which some have shown both GC-rich regions and polypyrimidine and polypurine tracts. 20,21 From our findings we suggest that the sequence similarities (80%) between the two chromosomes flanking the breakpoints as well as the surrounding polypurine and polypyrimidine tracts are predisposing factors for the reciprocal translocation. Recombination-associated sequence motifs have been shown to be over-represented at translocation breakpoints, including DNA polymerase core elements (frameshift hotspots) and heptamer recombination signals.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, translocation breakpoints are GC-rich (Abeysinghe et al, 2003) and oxidative damage is predominantly detected in GC-rich sequences (Akman et al, 2000). Thus, it is tempting to speculate that clustered oxidative damage may generate multiple DNA lesions in a short DNA fragment, which pose a serious obstacle for replication forks and may result in a DSB.…”
Section: Generation Of Dsbsmentioning
confidence: 99%
“…Multiple studies have identified associations between retrotransposons and chromosome rearrangements, including studies in mammalian cells revealing that retrotransposons are often found at breakpoint junctions of translocations and deletions present in tumor cells or cells derived from individuals with inherited disorders (Abeysinghe et al 2003;Florl and Schulz 2003). In Figure 2, respectively.…”
Section: Discussionmentioning
confidence: 99%